Determinants of online brand communities' and millennials' characteristics: A social influence perspective. Issue 5 (5th March 2021) - Ozuem, Wilson; Willis, Michelle; Howell, Kerry; Lancaster, Geoff; Ng, Raye
Abstract: Online communities have evolved to allow larger numbers of individuals to interact with other users to form a collective virtual environment influenced by members within the community. Existing studies on online brand communities (OBCs) tied millennials' participation and interactions to a unidimensional view. Specifically, OBCs scholars generally aggregate individual millennials' participation and commitment, ignoring the variance among the demographic cohort. Our exploration challenges not only the existing ensemble interpretation within studies of OBC but also the characterisation of millennials' burgeoning participation in OBCs. Unlike other competing epistemologies, the authors developed a conceptual framework that links a holistic set of OBCs' characteristics (brand sentiment, identification with source, affirmative experience, conspicuous effect) to consumers' perceptions in the fashion sector. Drawing on social influence theory along with a constructivist perspective, we conducted fine‐grained in‐depth interviews to explore millennials' participation in online communities and brand perceptions in the fashion industry. The main findings reveal four categories of customer engagement in OBCs (bias situators, sugar‐coaters, rationalisers, judgmentalists). These key categories are explored to create a framework for future research in this area, and further contribute to the field of online brand engagement, particularly in the fashion industry.